Analisis Wacana Kritis tentang Perempuan di Masa Pandemi Covid-19 pada Media Alternatif Magdalene.co - Firly Fenti; Aryo Subarkah Eddyono (Komunikasiana: Journal of Communication Studies, 2021)
Magdalene.co as an alternative media for women seeks to be a space for women to voice their interests, especially when this pandemic makes their position worse. The purpose of this study is to find out how Magdalene.co carries out women's discourse in the news about Covid-19 on the Issue channel. This research method is qualitative using critical discourse analysis from Sara Mills. The result of this research show that women are positioned as subjects and also objects. For discourse, Magdalene.co discusses women as those who are more severely affected by the corona pandemic, especially on the social and economic side.On the social side, it is discussed women are more vulnerable to experiencing domestic violence and experiencing burnout due to their dual roles. Meanwhile, on the economic side, women discourse as parties who are more likely to experience layoffs, so they are vulnerable to falling into poverty in this pandemic situation. The discourse carried out by Magdalene.co also illustrates the ideology of Magdalene.co as an alternative medium for women who hold the ideology of feminism.  Magdalene.co sebagai media alternatif perempuan berupaya menjadi ruang alternatif bagi perempuan dalam menyuarakan kepentingannya, terutama saat pandemi Covid-19. Ketika Covid-19 mulai merebak, Magdalene.co menampilkan beragam artikel yang menggambarkan situasi perempuan di tengah pandemi Covid-19. Penelitian ini menjawab bagaimana Magdalene.co mewacanakan perempuan dalam pemberitaan seputar Covid-19 di kanal Issue. Metode yang digunakan adalah analisis wacana kritis Sara Mills. Hasil penelitian menunjukkan bahwa perempuan diposisikan sebagai pihak yang terdampak efek pandemi Covid-19 lebih parah, terutama dalam konteks sosial dan ekonomi. Aspek sosial, perempuan rentan mengalami KDRT dan mengalami burnout akibat peran ganda mereka. Aspek ekonomi, perempuan juga merupakan pihak yang lebih berpotensi mengalami PHK sehingga rentan jatuh miskin. Pewacanaan tersebut amat tekait dengan ideologi Magdalene.co sebagai media alternatif perempuan yang memperjuangkan suara perempuan